NEUROENDOCRINE CARCINOMA PARU DENGAN PRESENTASI SINDROM VENA KAVA SUPERIOR: LAPORAN KASUS DAN TINJAUAN PUSTAKA - Desi Aliefia (Nusantara Hasana Journal, 2025)
Neuroendocrine carcinoma (NEC) is a heterogeneous group of neoplasms originating from neuroendocrine cells in the lung. High-grade subtypes such as small cell lung carcinoma (SCLC) and large cell neuroendocrine carcinoma (LCNEC) are characterized by rapid growth, early metastasis, and a poor prognosis. Early diagnosis through minimally invasive cytology procedures such as transthoracic needle aspiration – rapid on-site evaluation (TTNA-ROSE) is crucial for management. We report a 54-year-old man, a heavy smoker, who presented with progressive shortness of breath, productive cough, hoarseness, chest pain, and night sweats. A chest radiograph revealed a mediastinal mass. TTNA-ROSE, lymph node FNA, and core biopsy demonstrated typical cytomorphology of NEC with salt-and-pepper chromatin, molding, and background necrosis. Immunocytochemistry revealed synaptophysin positivity in >50% of tumor cells. The patient underwent radiotherapy but experienced clinical deterioration on follow-up. The TTNA-ROSE procedure facilitated the early diagnosis of NEC by assessing sample adequacy and expediting additional testing. Differential diagnoses include thymic SmCC, mediastinal lymphoma, Ewing sarcoma/PNET, metastatic SmCC from other organs, and poorly differentiated NSCLC. Current therapies include platinum-based chemotherapy, immunotherapy (pembrolizumab, nivolumab), somatostatin analogs (octreotide, lanreotide), and targeted therapies such as everolimus. The prognosis for NEC remains poor, with a median survival of 12–18 months in SCLC. This case emphasizes the critical role of TTNA-ROSE and immunocytochemistry in the diagnosis of pulmonary NEC. Early diagnosis and a multidisciplinary approach are necessary to improve patient outcomes.